(untitled) (Herald of Journalism, 2019)
This article analyzes and compares scientific, theoretical, and everyday phenomena. In general, the idea of creating a brand depends on the current demand: whether it has its own needs or not, and how effective it is for the consumer. Were identified features of our country, emphasizing the degree of for-mation, growth and development of the national brand. A link to the theme “The influence of national branding on the formation of the image of Kazakhstan” was the essence of the concept, and the emphasis on the modern features of the brand became the main object of the article. The importance and meaning of the formation of a national brand in the country were taken into account. The purpose of the article is the scientific relevance associated with branding and a set of activi-ties aimed at creating, developing and maintaining completely new technologies. According to their scientific and social significance, the article used the methods of reporting and descriptions, as well as comparison and analysis of the facts received from the media. The study took into account some facts of scientific interest on the concept of trends in the domestic brand. The article focuses on the relevance of the topic. The scientific relevance of this topic is also a subject of discussion: is it in demand today, is it needed, does it have concrete effectiveness for the consumer or not. The degree, growth and develop-ment of the national brand in our country were analyzed and presented in the article. One of the main goals of the article is to determine the importance and significance of the formation of a national brand in our country.